Cannabinoid 1/2 Receptor Activation Induces Strain-Dependent Behavioral and Neurochemical Changes in Genetic Absence Epilepsy Rats From Strasbourg and Non-epileptic Control Rats - De Deurwaerdère, Philippe; Casarrubea, Maurizio; Cassar, Daniel; Radic, Manuela; Puginier, Emilie; Chagraoui, Abdeslam; Crescimanno, Giuseppe; Crunelli, Vincenzo; Di Giovanni, Giuseppe (Frontiers in Cellular Neuroscience, 2022)
Childhood absence epilepsy (CAE) is characterized by absence seizures which are episodes of lack of consciousness accompanied by electrographic spike-wave discharges. About 60% of children and adolescents with ASs are affected by major neuropsychological comorbidities, including anxiety. Endocannabinoids and monoamines are likely involved in the pathophysiology of these CAE psychiatric comorbidities. Here, we show that the synthetic cannabinoid receptor type 1/2 (CB1/2R) agonist WIN 55,212-2 (2 mg/kg, i.p.) has a strain-dependent effect on anxiety-like and motor behavior and cerebral monoaminergic levels in Genetic Absence Epilepsy Rats from Strasbourg (GAERS) and their non-epileptic control (NEC) rat strain. Using quantitative and Temporal-Pattern analysis, we found that WIN 55,212-2 did not affect the emotional status of GAERS but it was anxiolytic in NEC. Conversely, WIN 55,212-2 had a sedative effect in GAERS but was ineffective in NEC. Moreover, vehicle-treated GAERS are more motivated to explore by implementing more complex and articulated strategies. These behavioral changes correlate with the reduction of 5-HT in the hippocampus and substantia nigra (SN) and noradrenaline (NA) in the entopeduncular nucleus (EPN) in vehicle-treated GAERS compared to NEC rats which could contribute to their low anxiety status and hypermotility, respectively. On the other hand, the increased level of NA in the EPN and 5-HT in the SN is consistent with an activation of the basal ganglia output-mediated motor suppression observed in WIN 55,212-2-treated GAERS rats. These data support the view of a strain-dependent alteration of the endocannabinoid system by adding evidence of lower emotional responsiveness and a basal ganglia hypersensitivity to cannabinoids in GAERS compared to NEC rats.